2017
DOI: 10.3390/ijms18091911
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Antioxidant Systems and Storability of Two Plum Cultivars by Preharvest Treatments with Salicylates

Abstract: In this research the effect of salicylic acid (SA), acetylsalicylic acid (ASA), and methylsalicylate (MeSA) treatments, applied as a foliar spray during on-tree plum development, on fruit quality attributes, bioactive compounds, antioxidant activity, and the activity of the antioxidant enzymes at harvest and after long-term cold storage was evaluated in two plum cultivars (“Black Splendor”, BS, and “Royal Rosa”, RR). At harvest, plum quality parameters, such as weight, total phenolics (including anthocyanins, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 54 publications
(100 reference statements)
7
19
0
2
Order By: Relevance
“…Similar effects of salicylate preharvest treatments were reported in plum [18,19]. In addition, SA, ASA and MeSA are natural compounds in plants which are recognized as GRAS (generally recognized as safe) for the United States Food and Drug Administration (FDA) and previous reports showed that fruit treatments with salicylates do not impart taste or off-flavor to fruit, although some sensory attributes, such as sweetness and firmness, increased [15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 64%
See 1 more Smart Citation
“…Similar effects of salicylate preharvest treatments were reported in plum [18,19]. In addition, SA, ASA and MeSA are natural compounds in plants which are recognized as GRAS (generally recognized as safe) for the United States Food and Drug Administration (FDA) and previous reports showed that fruit treatments with salicylates do not impart taste or off-flavor to fruit, although some sensory attributes, such as sweetness and firmness, increased [15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 64%
“…Moreover, SA, ASA, or MeSa treatments of sweet cherry trees, at 0.5, 1 and 2 mM concentrations, applied at key points of fruit development increased fruit quality attributes at harvest, such as weight, firmness and content of bioactive compounds namely phenolics, including anthocyanins, which were maintained during storage [15][16][17]. Similar effects of salicylate preharvest treatments were reported in plum [18,19]. In addition, SA, ASA and MeSA are natural compounds in plants which are recognized as GRAS (generally recognized as safe) for the United States Food and Drug Administration (FDA) and previous reports showed that fruit treatments with salicylates do not impart taste or off-flavor to fruit, although some sensory attributes, such as sweetness and firmness, increased [15][16][17][18][19].…”
Section: Introductionsupporting
confidence: 62%
“…Decreases in Hue color index show an intensification of purple color of plum skin, which usually occurs during ripening, either on tree or during storage (Martínez-Esplá et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Також саліцилова кислота відіграє основну роль у рості і розвитку рослин. Її дія пов'язана з захисними реакціями та забезпеченням захисту від атаки збудників фізіологічних хвороб [5,[7][8][9]. Обробка плодів саліциловою кислотою знизила розпад, викликаний грибом Botrytis cinerea, у томатах та сприяла затримці процесу достигання [6].…”
unclassified
“…Обробка плодів саліциловою кислотою знизила розпад, викликаний грибом Botrytis cinerea, у томатах та сприяла затримці процесу достигання [6]. Крім того, використання саліцилової кислоти сприяло зменшенні пошкоджень слив та персика [7].…”
unclassified